1998
DOI: 10.1128/iai.66.9.4450-4460.1998
|View full text |Cite
|
Sign up to set email alerts
|

Early Events in Phagosome Establishment Are Required for Intracellular Survival ofLegionella pneumophila

Abstract: During infection, the Legionnaires’ disease bacterium,Legionella pneumophila, survives and multiplies within a specialized phagosome that is near neutral pH and does not fuse with host lysosomes. In order to understand the molecular basis of this organism’s ability to control its intracellular fate, we have isolated and characterized a group of transposon-generated mutants which were unable to kill macrophages and were subsequently found to be defective in intracellular multiplication. These mutations define a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…In contrast, . 90% of the phagosomes containing either dead bacteria or viable icm/dot mutant bacteria fuse and form phagolysosomes (Horwitz, 1987;Roy et al, 1998;Wiater et al, 1998). Thus, the ability of the bacteria to influence the fusion properties of the phagosome is key to the ultimate fate of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, . 90% of the phagosomes containing either dead bacteria or viable icm/dot mutant bacteria fuse and form phagolysosomes (Horwitz, 1987;Roy et al, 1998;Wiater et al, 1998). Thus, the ability of the bacteria to influence the fusion properties of the phagosome is key to the ultimate fate of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Legionella pneumophila wild-type but not icm/dot mutant bacteria block maturation of the phagosome within minutes after internalization (Roy et al, 1998;Wiater et al, 1998). This finding prompted us to investigate whether phagocytosis was also affected by the pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cell -chlamydial inclusion Avoids lysosome fusion by diverting chlamydial inclusion from normal vesicular trafficking pathway (Hackstadt et al, 1997) Coxiella burnetii Macrophage, epithelial cell, fibroblast -acidic vacuole with markers of autophagy Exploits autophagic pathway, acid tolerant (Raoult et al, 1990;Gutierrez et al, 2005) Legionella pneumophila Macrophage -initially found in autophagosome, then in lysosome Modulates autophagic pathway, delays fusion with lysosomes (Andrews et al, 1998;Wiater et al, 1998;Amer and Swanson, 2005;) Listeria monocytogenes Macrophage, epithelial cell, fibroblast -cytosol Delays fusion with lysosomes, escapes from phagosome (Gaillard et al, 1987;Tilney and Portnoy, 1989;Henry et al, 2006) Mycobacterium tuberculosis Macrophage -modified early endosome Inhibits phagolysosome fusion, resistant to RNI (Flynn and Chan, 2003) Salmonella enterica ser. Typhimurium Macrophage, epithelial cell -Salmonella-containing vacuole (acquires LAMP1 but inhibits fusion with lysosomes) Modulates fusion with lysosomes, inhibits recruitment of phagocyte oxidase, resistance to antimicrobial peptides (Vazquez-Torres et al, 2000;Ernst et al, 2001;Holden, 2002) innate immune functions (Miyauchi et al, 1985;Radons et al, 1994).…”
Section: Chlamydia Trachomatismentioning
confidence: 99%
“…A type IVb secretion system encoded by 24 different dot and icm genes plays a central role in the modulation of host cell functions by Legionella (Segal and Shuman, 1997;Vogel et al ., 1998). Mutant Legionella that have a non-functional Dot/Icm system are unable to modulate vacuole transport (Marra et al ., 1992;Berger and Isberg, 1993;Swanson and Isberg, 1996;Andrews et al ., 1998;Roy et al ., 1998;Wiater et al ., 1998). Most Legionella dot and icm mutants reside in vacuoles that undergo endocytic maturation and fail to recruit ER-derived vesicles, resulting in a severe intracellular growth defect.…”
Section: Introductionmentioning
confidence: 99%